1980
DOI: 10.1093/jac/6.suppl_a.161
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and immunological aspects of therapy with cefotaxime and other cephalosporins

Abstract: Immunogenicity and allcrgcnicity studies in rodents show that cefotaxime and cefuroxime are less immunogenic than benzylpenicillin or the semisynthetic penicillins. Cross-reactions of these antibiotics with benzylpenicilloyl-specific animal and human IgE antibodies appear minimal. Some cross-reactivity at the level of cell-mediated allergic reactions may, however, be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Concentrations from 10 to 30 mg/mL have been recommended for intra‐dermal testing with some cephalosporins [46]. Data suggest that different patterns of positive responses may occur; while some cases develop cross‐reactivity between similar side chains [40, 43, 47], others experience a selective skin response to one cephalosporin only, and in others cross‐reactivity between penicillins and cephalosporins seems to occur [48, 49].…”
Section: Skin Testing With Other Betalactamsmentioning
confidence: 99%
“…Concentrations from 10 to 30 mg/mL have been recommended for intra‐dermal testing with some cephalosporins [46]. Data suggest that different patterns of positive responses may occur; while some cases develop cross‐reactivity between similar side chains [40, 43, 47], others experience a selective skin response to one cephalosporin only, and in others cross‐reactivity between penicillins and cephalosporins seems to occur [48, 49].…”
Section: Skin Testing With Other Betalactamsmentioning
confidence: 99%
“…3O Reports of changes in hematologic parameters have been sporadic. There have been occasional reports of decreased hemoglobin6*Ie2 or positive Coomb's tests.37 Gold did not notice such changes in any Of her 77 patients.% Eosinophilia (2 500 mm3) has been reported by [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] Gold observed eosinophilia in 14% of those children treated for 5 days or less and in 32% of those treated for longer Also obselved in Gold's series was neutro-Penis (< 1 500/mm3 in 18% of 28 children treated for more than 5 days with cefur~xime.~~ The clinical significance of these hemtologic changes is not ap-Parent. Follow-up studies have shown normalization Of hematologic parameters once therapy is discontinued.…”
Section: Side Effects and Toxicitymentioning
confidence: 99%